2020
DOI: 10.3390/biom10020223
|View full text |Cite
|
Sign up to set email alerts
|

Oral HPV16 Prevalence in Oral Potentially Malignant Disorders and Oral Cavity Cancers

Abstract: The role of human papillomavirus type 16 (HPV16) in oral potentially malignant disorders (OPMD) and oral cavity carcinoma (OC) is still under debate. We investigated HPV16 prevalence in unstimulated saliva, oral rinse samples, oral swabs and tumour biopsies collected from OPMD (n = 83) and OC (n = 106) patients. HPV16 genotype, viral load, physical status (episomal vs. integrated) and tumour p16INK4a expression were determined. Oral HPV16 prevalence was higher in OC than in OPMD, but this difference was not st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Salivary oral rinse samples of this individual were collected at baseline, 6, 12, 36 month, and 2 weeks after his bilateral tonsillectomy using previously published method (8)(9)(10). Briefly, participants were asked to swish and gargle for 1-2 min with 2 × 10 mL volumes of 0.9% saline, prior to expectorating the rinse sample into a 50 mL falcon tube.…”
Section: Clinical Specimens' Collection and Processingmentioning
confidence: 99%
“…Salivary oral rinse samples of this individual were collected at baseline, 6, 12, 36 month, and 2 weeks after his bilateral tonsillectomy using previously published method (8)(9)(10). Briefly, participants were asked to swish and gargle for 1-2 min with 2 × 10 mL volumes of 0.9% saline, prior to expectorating the rinse sample into a 50 mL falcon tube.…”
Section: Clinical Specimens' Collection and Processingmentioning
confidence: 99%
“…A growing body of evidence has suggested various means for establishing reliable and effective biomarkers for liquid biopsy screenings [ 24 , 25 ]. Due to the variability in standardized biomarkers, such as oral human papillomavirus (HPV) infection [ 26 , 27 ], focus has recently been placed on validation of exosomal and extracellular vesicle-derived microRNAs as potential biomarkers for liquid biopsy cancer screening, including those of oral cancers [ 28 , 29 ]. Based on this information, the primary objective of this study was to determine if oral cancers produce exosomes or extracellular vesicles containing miR-365, which might be useful as a potential screening tool, as was recently demonstrated in advanced breast cancers [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, salivary HPV DNA has demonstrated to be a good marker for detecting HPV in oropharyngeal cancer, as a high agreement between salivary HPV16 DNA infection and tumor p16 expression has been observed [51][52][53]. However, a recent study revealed a lower sensitivity for identifying p16-positive oral cancer patients through salivary HPV, which may indicate a limited involvement of HPV16 in oral carcinogenesis [54]. Interestingly, our study reviewed the different salivary HPV genotypes identified in oral and oropharyngeal carcinomas, providing additional evidence on the co-existence of multiple HPV types during carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%